Peningkatan Literasi Digital Siswa SMP melalui Asesmen Berbantuan “GALAKSI” Terintegrasi Augmented Reality pada Materi Sistem Tata Surya - Bunga Lady Aliza; Fahmi Fatkhomi; Mobinta Kusuma; Bayu Widiyanto (Mataram University, 2026)
Digital literacy is a fundamental competency that junior high school students need to master. However, science assessment practices in schools are still largely conventional and have not been integrated with interactive digital media, limiting their potential to foster students' digital literacy. This study aimed to determine the improvement in students' digital literacy after the implementation of assessment assisted by the